Kajian Implementasi Sistem Manajemen Keselamatan Pertambangan Dalam Rangka Meningkatkan Performa Keselamatan dan Kesehatan Kerja Tambang Bijih Emas Bawah Tanah di PT. Dempo Maju Cemerlang, Kabupaten Pesisir Selatan, Provinsi Sumatera Barat - Jumarinda Jumarinda; Fadhilah Fadhilah (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT. Dempo Maju Cemerlang is one of the gold mining companies that implement an underground mining system. The mining safety management program has not been fully implemented. This research aims to find out the percentage of application of Mining Safety Management System, accident statistics of work frequency rate and severity rate, as well as potential hazards in some areas of work that can cause accidents as well as reveal hazard control in the form of Job Safety Analysis (JSA). Data collection techniques use questionnaires, interviews, and observations of work activities. The results of the questionnaire analysis of the overall implementation level of the mining safety management system at PT. Dempo Maju Cemerlang based on the calculation of the Likert scale is 80.9%. With 84.2% policy element criteria, 81.3% planning element, 83.7% organizational and personnel elements, 81.1% implementation element, 80% evaluation and follow-up element, 75.6% documentation element, and 75.3% management review element. The frequency rate of accidents in 2019 was 44.18 with a severity rate of 166.55. JSA generated to identify workplace hazards in the main hole of SOD (South Ore Drift) in the work of the leg jack drill engine and the operation of diesel locomotives.Keywords:  Gold Mine, Mining Safety Management System, Accident Statistics, Potential Hazards, Job Safety Analysis